2017
DOI: 10.7717/peerj.4165
|View full text |Cite
|
Sign up to set email alerts
|

CD4 count and tuberculosis risk in HIV-positive adults not on ART: a systematic review and meta-analysis

Abstract: BackgroundCD4 cell count in adults with human immunodeficiency virus (HIV) infection (PLHIV) not receiving antiretroviral therapy (ART) influences tuberculosis (TB) risk. Despite widespread use in models informing resource allocation, this relationship has not been systematically reviewed.MethodsWe systematically searched MEDLINE, Aidsinfo, Cochrane review database and Google Scholar for reports in English describing TB incidence stratified by updated CD4 cell count in cohorts of HIV-positive adults (age ≥15 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 25 publications
4
38
0
1
Order By: Relevance
“…A meta-analysis estimated a 1.43-fold (95% credible interval: 1.16-1.88) increase in TB incidence per 100 cells per mm 3 decrease in CD 4 cell count. 16 In our study, the CD 4 counts of the HIV positive patients ranged between 4 and 338 cells/m³ (median 110 cells/m³); 92.6% of the patients had CD 4 counts of <200 cells/m³ and 25.9% had a CD 4 count of <50 cells/m³, indicating that a significant number of patients had profound immunosuppression at the time of investigation for symptomatic HIV/ TB disease. In a South African study, it was seen that 61.2% had CD4 cell counts <200 cells/μL, 82.7% had counts <350 cells/μL.…”
Section: Discussionmentioning
confidence: 53%
“…A meta-analysis estimated a 1.43-fold (95% credible interval: 1.16-1.88) increase in TB incidence per 100 cells per mm 3 decrease in CD 4 cell count. 16 In our study, the CD 4 counts of the HIV positive patients ranged between 4 and 338 cells/m³ (median 110 cells/m³); 92.6% of the patients had CD 4 counts of <200 cells/m³ and 25.9% had a CD 4 count of <50 cells/m³, indicating that a significant number of patients had profound immunosuppression at the time of investigation for symptomatic HIV/ TB disease. In a South African study, it was seen that 61.2% had CD4 cell counts <200 cells/μL, 82.7% had counts <350 cells/μL.…”
Section: Discussionmentioning
confidence: 53%
“…In this situation, the people in Lh would be more protected than people in Rh. However, if this were the case, we would observe many TB cases with high CD4 cell count that was contradicted by [ 30 , 44 ] that showed that about 90% of co-infected patients have CD4 cell count lower than 400 cells/μl and the risk of TB increases exponentially with the decline of CD4.…”
Section: Discussionmentioning
confidence: 82%
“…We have to emphasize that if people in Rh are more protected than people in Lh does require further investigation and verification with a different model and data set that at least includes information about CD4 cell count and HIV progression. Several papers [ 30 , 43 , 44 ] indicate that the risk of TB increase after CD4 cell counts starts to decline. Therefore, modeling for a short period of HIV infection in this paper overestimates the TB risk of people in Lh.…”
Section: Discussionmentioning
confidence: 99%
“…High viral load increased disease progression. The results of multivariate analysis showed that patients with CD4 levels less than 500 cells / mm 3 were at risk of being infected with 3,141 times compared to patients with CD4 levels more than 500 24 .…”
Section: Discussionmentioning
confidence: 97%